MODEL EVALUASI INTERNAL KOMPETENSI GURU BAHASA INGGRIS (MODEL_EIKGBI) SMA - Sahraini, Sahraini; Madya, Suwarsih (Graduate School, Universitas Negeri Yogyakarta in cooperation with Himpunan Evaluasi Pendidikan Indonesia (HEPI) Yogyakarta, 2015)
Studi ini bertujuan untuk: (1) mengembangkan model evaluasi kompetensi guru bahasa Inggris SMA yang dapat digunakan untuk mengidentifikasi kelebihan dan kekurangan guru dalam proses pemelajaran dan (2) mengetahui efektivitas implementasi evaluasi internal kompetensi guru bahasa Inggris SMA. Studi ini menggunakan metode penelitian dan pengembangan yang dikembangkan oleh Borg & Gall (1983, p.775). Subjek penelitian berjumlah 17 guru yang berasal dari 7 SMA di Sulawesi Selatan. Konstruk instrumen terdiri atas instrumen untuk mengevaluasi kompetensi guru bahasa Inggris dalam merencanakan pemelajaran, instrumen untuk mengevaluasi kompetensi guru dalam melaksanaan proses pemelajaran, dan instrumen untuk mengevaluai kompetensi guru dalam mengevaluasi hasil proses pemelajaran. Hasil penelitian menunjukkan bahwa instrumen yang dikembangkan dapat digunakan untuk mengevaluasi kompetensi guru bahasa Inggris. Untuk mengetahui sejauh mana tingkat efektivitas Model Evaluasi Internal Kompetensi Guru Bahasa Inggris SMA, model ini kemudian dievaluasi oleh teman sejawat guru bahasa Inggris dan guru bahasa Inggris itu sendiri. Mereka menyimpulkan bahwa komponen dari model tersebut adalah komprehensip, praktis, ekonomis, dan telah didukung oleh instrumen yang valid dan reliabel.Kata kunci: evaluasi internal, model evaluasi, kompetensi guru INTERNAL EVALUATION MODEL OF ENGLISH TEACHERS' COMPETENCY (IEMET) FOR SENIOR HIGH SCHOOLAbstractHigh School that can be used to identify the teacher's strengths and weaknesses in learning and teaching processes and (2) find out the implementation effectiveness of the Internal Evaluation Model of English Teachers' Competency for Senior High School. This study used research & development methods by following the pattern of phases developed by Borg & Gall (1983, p.775). The subjects of this study were seventeen English teachers from seven Senior High Schools in South Sulawesi. The constructs of instruments consist of the instrument to evaluate English teachers' competency in planning the materials, teachers' competency in teaching and learning processes, and teachers' competency in evaluating the result of teaching and learning processes. An Exploratory Factor Analysis (EFA)was used to analyze he instrument. The result showed the score of KMO- MSA (Kaiser-Meyer-Olkin Measure of Sampling Adequacy) > 0.5, Bartlett's Test of Sphericity â‰¤ 0.05, and the score of items total correlation rit<0.3. Meanwhile, the analysis of rater agreement used was Generalizability of Variants (GENOVA). The interrater correlation showed that the score of G study was > 0.70. This result shows the instruments have fulfilled the requirement to evaluate the English teacher's competency. In order to know to what extent the effectiveness of the Internal Evaluation Model of English teachers' competency for Senior High School, the model was then evaluated by peer and the English teacher itself. They concluded that the components of the model were comprehensive, practical, economical, and were supported by instruments that valid and reliable.Keywords: internal evaluation, evaluation model, teachers' competency